One Pot Multicomponent Synthesis of Anti-inflammatory Active Tetrahydrofuro[3,2-c]pyridinone-2-carboxylate Derivatives - Tangeti, Venkata Swamy; Reddy, Boyi Harika; Evangeline, K. Sharon (Asian Journal of Chemistry, 2017)
A novel, one-pot method has been developed for the synthesis of tetrahydrofuro[3,2-c]pyridine-2-carboxylate derivatives via cascade four-component condensation of 6-methyl, 4-hydroxy pyranone, aryl amines, aromatic aldehydes and pyridinium ylide, in presence of triethylamine as a catalyst under ethanol reflux conditions. It affords the corresponding product in high yield (78-92 %) with short reaction time (15-25 min).The anti-inflammatory activity of these compounds was determined. Out of the 17 synthesized compounds, compounds 5j, 5k, 5l, 5m and 5n were excellent inhibitors of TNF-a and IL-6, COX-2, b-glucuronidase.